Water in Paraguay: between life, death and possible rebirth - Dionisi, Maria Gabriella (Oltreoceano - Rivista sulle migrazioni, 2024)
Over the centuries Paraguay has established a conflictual and indissoluble relationship with its two main rivers, the Paraguay River, which divides the country in two regions, and the Paraná, which marks its eastern border. Both these impressive rivers have, indeed, played a crucial role in the life and development of the country: they have been not only privileged access routes for the conquistadores and the immigrants, sites of bloody commercial and political clashes, and painful routes to exile for the opponents of various regimes, but also sources of livelihood and profit as well as agents of destruction during floods. At times, their presence was not sufficient to avoid frequent periods of drought, which fueled conflicts, such as the well-known “War of Thirst” against Bolivia, fought between 1932 and 1935 in defense of the Chaco region. As Jean Andreu has aptly noted in an essay on Augusto Roa Bastos, all these aspects are tackled with in the works of Paraguayan writers. In an attempt to provide some examples of the different interpretations that writers give on the theme, this article analyses some excerpts from stories, novels and poems by well-known Paraguayan writers, like Augusto Roa Bastos, Renée Ferrer, José-Luis Appleyard and Javier Viveros, and poets like Eloy Fariña Núñez, Victorino Abente y Lago and Elvio Romero.